Результаты уточнения динамики температуры подреакторной плиты и суммарного тепловыделения из зоны локализации ядерно-опасных скоплений в помещении 305/2 объекта "Укрытие" ЧАЭС - Михайлов, А.В.; Дорошенко, А.В. (Проблеми безпеки атомних електростанцій і Чорнобиля, 2017)
Подведены итоги многолетних исследований динамики температуры на периферии ядерно-опасных скоплений (ЯОС), локализованных в зоне глубокого проплавления подреакторной плиты в юго-восточном квадранте помещения 305/2 объекта «Укрытие» ГСП ЧАЭС. Проанализированы данные измерений, полученные автоматизированными системами контроля за период 1989 - 2015 гг. Дана математическая оценка обнаруженных трендов и температурных градиентов на пути рассеяния тепла из зоны ЯОС в окружающую среду. На основе последних результатов измерений проведено уточнение ранее полученных данных. Масса урана, сконцентрированного в зоне ЯОС, оценена с учетом вклада в интегральное тепловыделение дополнительного внутреннего источника тепла, частично компенсирующего падение мощности остаточного тепловыделения отработавшего топлива. Наведено підсумки багаторічних досліджень за динамікою температури на периферії ядерно-небезпечних скупчень (ЯНС), локалізованих у зоні глибокого проплавлення підреакторної плити в південно-східному квадранті приміщення 305/2 об’єкта «Укриття» ДСП ЧАЕС. Проаналізовано дані вимірювань, що були отримані автоматизованими системами контролю за період 1989 - 2015 рр. Наведено математичну оцінку виявлених трендів і температурних градієнтів на шляху розсіяння тепла із зони ЯНС у навколишнє середовище. На основі останніх результатів вимірювань проведено уточнення раніше отриманих даних. Масу урану, що сконцентрована в зоні ЯНС, оцінено з урахування внеску в інтегральне тепловиділення додаткового внутрішнього джерела тепла, частково компенсуючого падіння потужності остаточного тепловиділення палива. Continuous temperature monitoring at periphery of nuclearly hazardous clusters (NHC) in Chernobyl NPP оbject “Ukryttya” southeast quadrant of room 305/2 was being carried out from November 1988 to 2015 with using “Finish” Information and Measurement System. This work was carried out in order to clarify earlier conclusions concerning regularities of thermal regime formation around the NHC until NSC creation. This work was aimed at creating initial dataset for further evaluation of NHC state within NSC conditions. The methods of statistical analysis of data on temperature of sub-reactor slab (elevations +8.00 - +9.30) were used, in reactor shaft (elevation +12.00), in Central Hall (elevation +30.00 - +34.50) and in air (environmental) temperature beyond оbject “Ukryttya” limits. The research period has covered the time interval from November 1988 before December 2015. To make a comparative analysis of time dependences of concrete temperature at different distances from NHC boundaries, mean annual values were given (normalized) to the values calculated for 1991 year. Analogously normalized data for temporary characterization of fuel afterheat and environmental mean annual temperature values were overlapped on obtained picture. The results obtained in this work made it possible creating an integral picture of temperature dynamics at different distances from NHC boundaries in room 305/2 during survey period from 1991 to 2015 years. Earlier obtained values of temperature gradients and its change’s trends at NHC periphery, which were observed before the NSC was installed in its design position, were refined. More accurate data were obtained on degree of impact of additional internal heat source onto total heat release from the NHC area (not more than 0.071 kW/t of uranium in 2016 year) and uranium mass concentrated in deep burn-through place of sub-reactor slab (up to 18 ± 5 tons). Based on the data obtained and design value of spent nuclear fuel afterheat (0.208 kW/t), total rate of heat source hidden under the layers of black lava-like fuel-containing masses and 1986 year concrete in southeast quadrant of room 305/2 was estimated at 5.1 ± 1.4 kW/h (as of November 2016).